INFLUENCE OF EMOTIONAL ENGAGEMENT COUNSELING ON MARRIAGE STABILITY OF COUPLES IN PENTECOSTAL CHURCHES IN KAMPALA, UGANDA. A CROSS-SECTIONAL STUDY. - Nyamahunge, Grace Kyokuhaire; Kiyingi , Frank Pio (SJ Insights, 2025)
Background Pre-marital counseling was conceptualized as a specific type of systemic counseling aimed at assisting couples who are considering marriage. The study aims to assess the influence of emotional engagement counseling on the marriageability of couples in Pentecostal Churches in Kampala, Uganda. Methodology A cross-sectional research design using quantitative approaches to collect data from different categories of respondents at a single point in time. The study employed descriptive correlation study was used to determine the relationship between pre-marital counseling and the marriage stability of couples. Results Emotional engagement counseling has a very weak positive and significant influence on the marital stability of couples in Pentecostal churches in KampalaCity, r = 0.167**. When the provision of emotional engagement counseling increases by one unit, the marital stability of couples in Pentecostal churches also changes positively or increases by one unit. However, at a very low level. The P-value was lower than that significance level (0.035 < 0.05) when r2 was calculated, 0.0278 (100), which means that emotional engagement counseling influences positively the marital stability of couples in a Pentecostal church in Kampala, Uganda at 2.78%. For hypothesis two testing, results provided a P-value of 0.035 which was less than the 0.05 level of significance. Conclusion Emotional engagement counseling had a very weak, positive, and significant influence on the marital stability of couples in Pentecostal churches in Kampala City. The fact that the P-value was low at the significance level, the researcher rejected the null hypothesis and considered the alternative one. Recommendation Couples should be encouraged to partake in emotional engagement counseling as it has a significant influence on marital stability